Minimally invasive hysterectomy for stage IA cervical carcinoma: a survival analysis of the National Cancer Database. Issue 8 (6th May 2021) - Nasioudis, Dimitrios; Byrne, Maureen; Ko, Emily M; Haggerty, Ashley F; Cory, Lori; Giuntoli II, Robert L; Kim, Sarah H; Latif, Nawar A
Abstract : Objective: To evaluate the outcomes of minimally invasive surgery for patients with stage IA cervical carcinoma undergoing hysterectomy. Methods: Patients with pathological stage IA (IA1, IA2, IA not otherwise specified) squamous, adenocarcinoma, adenosquamous carcinoma of the cervix, no history of another tumor, who underwent radical or simple hysterectomy with known mode of surgery, diagnosed between 2010 and 2015 with at least 1 month of follow-up, were drawn from the National Cancer Database. Comparisons of demographic and clinicopathologic characteristics were made with the χ 2 test. The impact of minimally invasive surgery (robotic-assisted or traditional laparoscopic) on overall survival was assessed with the log-rank test following generation of Kaplan–Meier curves. A Cox model was constructed to control for confounders. Results: A total of 1930 patients were identified; the majority (73.3%, 1414 patients) had stage IA1 disease, while 458 (23.7%) patients had stage IA2, and 58 (3%) patients had stage IA not otherwise specified. In the present cohort, 685 patients (35.5%) had open, 438 patients (22.7%) had laparoscopic, and 807 patients (41.8%) had robotic-assisted laparoscopic hysterectomy. Patients who had an open approach were more likely to undergo lymphadenectomy (58.1% vs 52.7%, p=0.021) and have radical hysterectomy (42% vs 32.4%, p<0.001). Patients who had minimally invasive surgery had a shorter hospital stay (median 1 vs 3 days, p<0.001). There was no difference in overall survival between patients who had open and minimally invasive hysterectomy (p=0.87); 4-year overall survival rates were 97.7% and 98.6%, respectively. There was no difference in overall survival between the open and minimally invasive surgery groups for patients who had simple (p=0.61; 4-year overall survival rates 97.6% and 98.7%, respectively) or radical hysterectomy (p=0.70; 4-year overall survival rates 97.8% and 98.4%, respectively). After controlling for patient age, tumor histology, and presence of lymphovascular invasion, minimally invasive hysterectomy was not associated with worse survival (HR 0.94, 95% CI 0.49 to 1.81). In a sensitivity analysis, based on 3048 patients with clinical stage IA after controlling for confounders, minimally invasive surgery was not associated with worse survival than laparotomy (HR 1.06, 95% CI 0.65 to 1.72). Conclusions: In a large cohort of patients with stage IA cervical carcinoma, performance of minimally invasive hysterectomy was not associated with a detrimental effect on overall survival.